Digitalisasi Pendidikan Islam: Eksplorasi Pemanfaatan Media Pembelajaran di SMPN 2 Langgam - Epy Pujiaty; Enson Joko Purnomo (MAN 4 Kota Pekanbaru, 2026)
The rapid digitalization of education requires teachers to integrate technology into the learning process, including Islamic Religious Education. The use of digital learning media offers opportunities to enhance instructional effectiveness and align learning with the characteristics of digitally oriented students. This study aims to explore the utilization of digital learning media in Islamic Religious Education at SMP Negeri 2 Langgam, identify the challenges faced by teachers, and examine its impact on the learning process. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving Islamic Religious Education teachers and students. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the integration of digital media supports interactive learning, although its implementation is still constrained by uneven internet infrastructure and limited teacher digital literacy. This study contributes to the development of technology-based Islamic education learning practices relevant to contemporary educational demands and supports the enhancement of teachers’ digital literacy and pedagogical competence in the digital era.